Physical, thermal, antioxidant and antimicrobial properties of starches from corn, oat, and wheat enriched with Zataria essential oil. (July 2019) - Shahrokh, Zargham; Kavoosi, Gholamreza; Shakeri, Raheleh
Abstract: Some functional and physical properties of corn, oat, and wheat starch emulsions enriched with polysorbate-Zataria essential oil (ZEO) were investigated. Evaluation of physical properties of starch showed that polysorbate-ZEO decreased the particle size and viscosity of starch, but increased the zeta potential. Thus, polysorbate-ZEO prevents phase separation and precipitation of starch. Polysorbate-ZEO and starches containing polysorbate-ZEO exhibited antimicrobial and antioxidant activities. The activities were lower in the starch enriched with polysorbate-ZEO than polysorbate-ZEO alone. The most likely reason could be due to the encapsulation of ZEO in the starch chain. Differential thermal analysis (DTA) exhibited similar trends for starch and starch-ZEO, suggesting that ZEO had no significant effect on thermal stability. Fourier transform infrared spectroscopy (FTIR) showed that the spectral features of all starch emulsions were similar. Such similarity supports the assumption of non-covalent interactions between starch and ZEO. This study demonstrated the antioxidant and antibacterial capacities of starch enriched with ZEO as a potential antioxidant/antimicrobial ingredient. Corn, oat, and wheat starch increase the stability and bioavailability of ZEO while ZEO increases antioxidant and antibacterial activities of corn, oat, and wheat starch to make them functional foods. Graphical abstract: Image 1 Highlights: ZEO microencapsulated in corn, oat and wheat starch emulsions. ZEO decreased the particle size and viscosity of starch emulsions. ZEO interacted with starch polymer via non-covalent interactions. Polysorbate-ZEO and starches containing polysorbate-ZEO exhibited antimicrobial and antioxidant activities.